PENDETEKSIAN FRAUDULENT FINANCIAL REPORTING (FFR) MENGGUNAKAN RASIO-RASIO KEUANGAN - Winda Milasari; Dwi Ratmono (Diponegoro Journal of Accounting, 2019)
The purpose of this study is for examining financial ratios for detecting fraudulent financial reporting. Independent variables of financial ratios used in this study are leverage, profitability, asset composition, proportion of accounts receivable, proportion of inventory, liquidity and capital turnover. The dependent variable used is fraudulent financial reporting based on data violations of BAPEPAM VIII G7 regulations issued by Otoritas Jasa Keuangan (OJK) in 2011-2016.The research sample consist of 41 fraud companies and 41 non-fraud companies in the non-financial sector listed on the Indonesia Stock Exchange in 2007-2014. This type of data is secondary data and uses purposive sampling method to determine the sample. The data analysis uses logistic regression method.The results of the study show that leverage ratio variable have a positive and significant effect in detecting fraudulent financial reporting. However, the other financial ratios (profitability, asset composition, proportion of accounts receivable, proportion of inventory, liquidity and capital turnover) have no significant effect on fraudulent financial reporting.